The analysis of learning model of Q.S. Al Ma'un by K.H. Ahmad Dahlan in the film â€œsang pencerahâ€ - Carla Maretha; Dalman Dalman; Hesti Hesti (Universitas Muhammadiyah Surabaya, 2020)
Abstract. The learning practice of Q.S. Al Ma‘un by K.H. Ahmad Dahlan gives significantimpact on people civilization and Islamic education as depicted in the film ―SangPencerah‖. The success becomes a magnet which attracts the curiousity about how the, learning practice is conducted. In accordance with it, this research studies learning model of Q.S. Al Ma‘un by K.H. Ahmad Dahlan in the film ‗Sang Pencerah‘. This researh is conduccted with qualitative method. This research shows the learning model of Q.S. Al Ma‘un by K.H. Ahmad Dahlan is supported by the teaching process and the included elements of learnign model. This research resulted in 1) the teaching process of Q.S. Al Ma'un by K.H. Ahmad Dahlan in the film